Playing the complex game of social status in school – a qualitative study. Issue 1 (31st December 2020) - Joffer, Junia; Randell, Eva; Öhman, Ann; Flacking, Renée; Jerdén, Lars
ABSTRACT: Background: Research suggests that social status in school plays an important role in the social lives of adolescents and that their social status is associated with their health. Additional knowledge about adolescents' understanding of social hierarchies could help to explain inequalities in adolescents' health and guide public health interventions. Objective: The study aimed to explore what contributes to subjective social status in school and the strategies used for social positioning. Methods: A qualitative research design with think-aloud interviews was used. The study included 57 adolescents in lower (7 th grade) and upper secondary school (12 th grade) in Sweden. Subjective social status was explored using a slightly modified version of the MacArthur Scale of Subjective Social Status in school. Data were analyzed using thematic network analysis. Results: The participants were highly aware of their social status in school. Elements tied to gender, age, ethnicity and parental economy influenced their preconditions in the positioning. In addition, expectations on how to look, act and interact, influenced the pursue for social desirability. The way these different factors intersected and had to be balanced suggests that social positioning in school is complex and multifaceted. Conclusions: Because the norms that guided social positioning left little room for diversity, the possible negative impact of status hierarchies on adolescents' health needs to be considered. In school interventions, we suggest that norms on e.g. gender and ethnicity need to be addressed and problematized from an intersectional approach.